2019
DOI: 10.1093/aob/mcz207
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal variation in seed predation correlates with latitudinal variation in seed defensive and nutritional traits in a widespread oak species

Abstract: Background and Aims Classic theory on geographical gradients in plant–herbivore interactions assumes that herbivore pressure and plant defences increase towards warmer and more stable climates found at lower latitudes. However, the generality of these expectations has been recently called into question by conflicting empirical evidence. One possible explanation for this ambiguity is that most studies have reported on patterns of either herbivory or plant defences whereas few have measured bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…We found that herbivory and carnivory measured on standardised prey, including non‐native plant species/genotypes (Lu et al, 2019) or their seeds (Chen et al, 2017; Hargreaves et al, 2019), plasticine insect models (Roslin et al, 2017; Zvereva et al, 2019), non‐native live insect prey (Jeanne, 1979) and artificial bird nests (McKinnon et al, 2010), yield stronger latitudinal patterns than are obtained when predation is measured on natural prey, at least for ectothermic consumers. This difference can be explained by the latitudinal changes in local adaptations of native plant/prey, for example in anti‐herbivore defences in plant seeds (Chen et al, 2017; Moreira et al, 2020) and in the behavioural and life history anti‐predator adaptations in birds (Díaz et al, 2013; Freeman et al, 2020), whereas standardised models did not participate in evolution (Freeman et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We found that herbivory and carnivory measured on standardised prey, including non‐native plant species/genotypes (Lu et al, 2019) or their seeds (Chen et al, 2017; Hargreaves et al, 2019), plasticine insect models (Roslin et al, 2017; Zvereva et al, 2019), non‐native live insect prey (Jeanne, 1979) and artificial bird nests (McKinnon et al, 2010), yield stronger latitudinal patterns than are obtained when predation is measured on natural prey, at least for ectothermic consumers. This difference can be explained by the latitudinal changes in local adaptations of native plant/prey, for example in anti‐herbivore defences in plant seeds (Chen et al, 2017; Moreira et al, 2020) and in the behavioural and life history anti‐predator adaptations in birds (Díaz et al, 2013; Freeman et al, 2020), whereas standardised models did not participate in evolution (Freeman et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…An association between temperature and seed mucilage quantity has previously been reported and the authors attributed the cause to water stress (Teixeira et al., 2020). Additionally, higher seed predation pressure in warmer places (Moreira et al., 2020; Noroozi et al., 2016) could select for more tightly bound seeds as a defence against granivory. A correlation between mucilage and solar radiation has not been proposed in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Plant species at lower latitudes commonly experience higher rates of herbivory than plants growing further from the Equator (Coley & Barone, 1996; Lim et al., 2015; Moreira et al., 2018; Schemske et al., 2009) and thus tropical plant species may evolve higher levels of anti‐herbivore defences (Abdala‐Roberts et al., 2016; Hahn et al., 2019; Johnson & Rasmann, 2011; Pearse & Hipp, 2012). While early reviews reported patterns supporting these predictions (Coley & Aide, 1991; Coley & Barone, 1996; Dyer & Coley, 2002), several studies in recent decades have found either no evidence for a latitudinal gradient in herbivory and plant defences (Gaston et al., 2004; Moles et al., 2011; Moles & Westoby, 2003) or increase in herbivory and defences with latitude (Adams et al., 2009; Del‐Val & Armesto, 2010; Gaston et al., 2004; Martz et al., 2009; Moreira et al., 2018, 2020; Pennings et al., 2009; Stark et al., 2008; Woods et al., 2012). Given these inconsistencies, it is of great importance to identify the mechanisms underlying the substantial variation in herbivory and plant defences across latitudes, as herbivory is an important ecological process that modulates primary productivity by altering the recruitment, mortality and growth of plants.…”
Section: Introductionmentioning
confidence: 99%